PENGARUH KB SUNTIK 3 BULAN TERHADAP KENAIKAN BERAT BADAN DI POSKESDES KAMPAI KABUPATEN OGAN KOMERING ULU TAHUN 2020 - Willy Astriana (Jurnal Kesehatan Abdurrahman, 2021)
Data from the World Population Data Sheet in 2013, Indonesia is the 5th country in the world with an estimated population of 249 million. Among ASEAN countries, Indonesia, with the largest area in area, remains the country with the largest population, far above the other 9 member countries (Ministry of Health, Republic of Indonesia, 2014). This was to determine the effect of 3-month injection of family planning on weight gain in Poskesdes Kampai, Ogan Komering Ulu Regency. This study used an analytical survey method with a cross sectional approach. The population in this study were all mothers who were family planning acceptors at the Poskesdes Kampai, Ogan Komering Ulu Regency for the period August-November 2020 totaling 30 acceptors. Data analysis used univariate analysis and bivariate analysis using distribution tables and Chi-Square statistical tests, with a degree of confidence of 95%. In the bivariate analysis, it was found that there was a significant relationship between the effect of 3-month injection family planning on weight gain at the Poskesdes Kampai, Ogan Komering Ulu Regency in 2020. This was proven in the results of the chi-square statistical test p value 0.029 <0.05. There is a significant relationship between the effect of 3-month injection family planning on weight gain at the Poskesdes Kampai, Ogan Komering Ulu Regency in 2020.